New Insights Into the Relationships Within Subtribe Scorzonerinae (Cichorieae, Asteraceae) Using Hybrid Capture Phylogenomics (Hyb-Seq) - Hatami, Elham; Jones, Katy E.; Kilian, Norbert (Frontiers in Plant Science, 2022)
Subtribe Scorzonerinae (Cichorieae, Asteraceae) contains twelve main lineages and approximately 300 species. Relationships within the subtribe either at inter-or intrageneric levels were largely unresolved in phylogenetic studies to date, due to the lack of phylogenetic signal provided by traditional Sanger sequencing markers. In this study, we employed a phylogenomics approach (Hyb-Seq) that targets 1,061 nuclear conserved ortholog loci designed for Asteraceae and obtained chloroplast coding regions as a by-product of off-target reads. Our objectives were to evaluate the potential of the Hyb-Seq approach on resolving the phylogenetic relationships across the subtribe at deep and shallow nodes, investigate the relationships of major lineages at inter- and intrageneric levels, and examine the impact of the different datasets and approaches on the robustness of phylogenetic inferences. We analysed three nuclear datasets: exon only excluding all potentially paralogous loci, exon only including loci that were only potentially paralogous in 1–3 samples, exon plus intron regions (supercontigs), and the plastome CDS region. Phylogenetic relationships were reconstructed using both multispecies coalescent and concatenation (Maximum Likelihood and Bayesian analyses) approaches. Overall, our phylogenetic reconstructions recovered the same monophyletic major lineages and were successful in fully resolving the backbone phylogeny of the subtribe, while internal resolution of the lineages was comparatively poor. The results of our analyses were consistent with the topologies found in previous studies. The backbone topologies were largely congruent among all inferences, but, some incongruent relationships were recovered between nuclear and plastome datasets, representing cases of cytonuclear discordance. In light of the newly resolved phylogenies, a new infrageneric classification of Scorzonera in its revised circumscription is proposed.